2020
DOI: 10.31730/osf.io/c4xgs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General Collective Intelligence as the Emerging Paradigm in Human-Centric Design for Sustainability

Abstract: A recently developed framework for modelling cognition defines General Collective Intelligence or GCI as Collective Intelligence (CI) with general problem solving ability. Where CI uses the intelligence of crowds to optimize decision-making, a GCI must also optimize the choice of problem to solve. This framework represents a GCI as an adaptive problem solving system with problem solving segmented across a hierarchy of problem solving domains, one of which is adaptation through cooperation between functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As a specific example of the "Change of Components in Cooperation" pattern, the conceptual case study of a healthcare value chain in the US showed the potential to increase collective outcomes (impact on access to affordable healthcare) by up to 40% through development of GCI based healthcare and health insurance platforms [6]. As a specific example of the "Change of Targeted Outcome and Components of Cooperation" pattern, the conceptual case study of a "Design for Change -Nairobi" sustainable housing design challenged showed the potential for an increase collective in outcomes (impact on access to affordable sustainable housing) by a significant enough margin to impact poverty [7]. This impact on sustainable housing is expected to occur through research into semantic representation of designs, where that research might be incorporated into a "Collaborative Design Platform" which facilitates collaboration between a massively larger number of designers to discover higher impact outcomes in a far larger region of solution design space [7].…”
Section: Three Patterns For Radically Increasing Social Impactmentioning
confidence: 99%
“…As a specific example of the "Change of Components in Cooperation" pattern, the conceptual case study of a healthcare value chain in the US showed the potential to increase collective outcomes (impact on access to affordable healthcare) by up to 40% through development of GCI based healthcare and health insurance platforms [6]. As a specific example of the "Change of Targeted Outcome and Components of Cooperation" pattern, the conceptual case study of a "Design for Change -Nairobi" sustainable housing design challenged showed the potential for an increase collective in outcomes (impact on access to affordable sustainable housing) by a significant enough margin to impact poverty [7]. This impact on sustainable housing is expected to occur through research into semantic representation of designs, where that research might be incorporated into a "Collaborative Design Platform" which facilitates collaboration between a massively larger number of designers to discover higher impact outcomes in a far larger region of solution design space [7].…”
Section: Three Patterns For Radically Increasing Social Impactmentioning
confidence: 99%
“…As a specific example of the "Change of Components in Cooperation" pattern, the conceptual case study of a healthcare value chain in the US showed the potential to increase collective outcomes (impact on access to affordable healthcare) through development of GCI based healthcare and health insurance platforms [16]. As a specific example of the "Change of Targeted Outcome and Components of Cooperation" pattern, the conceptual case study of a "Design for Change -Nairobi" sustainable housing design challenged showed the potential for an increase collective in outcomes (impact on access to affordable sustainable housing) by a significant enough margin to impact poverty through research into semantic representation of designs, where that research might be incorporated into a "Collaborative Design Platform" that facilitates collaboration between a massively larger number of designers to discover higher impact outcomes in a far larger region of solution space [13].…”
Section: Table 1: Patterns In the Use Of Human-centric Functional Mod...mentioning
confidence: 99%
“…Patterns in the use of HCFM and GCI described in this paper (table 1) focus on significantly increasing societal impact for specific challenges that might be addressed through STEM [12], such as in civil engineering (sustainable housing) [13], computer science [15], health care informatics [16], and sustainable development [18]. Additional ongoing work continues to explore impacts in a wide range of of other disciplines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation